Analisis Dampak Lingkungan Pembangunan Drainase terhadap Aspek Sosial Ekonomi Masyarakat: Studi Kasus: Wilayah Jalan D.I Panjaitan Kecamatan Sungai Pinang Kota Samarinda - Putri, Wa; Ilham, Ilham; Sumarlin, Sumarlin (Universitas Muhammadiyah Kendari, 2023)
This study aims to analyze the socio-economic impact of drainage development on Jalan D.I Panjaitan, Sungai Pinang Subdistrict, Samarinda City. This study used a survey method by collecting primary data through questionnaires from 33 respondents affected by the drainage development. The social impact analysis evaluated people's views and responses to the drainage development. Meanwhile, the economic impact analysis involved an assessment of changes in the socioeconomic conditions of the community after the construction of the drainage. The research study showed that the majority of the community perceived their relationship with the development as unfavorable and expressed dissatisfaction with the impacts. A number of respondents also stated that the drainage development had caused social and economic disruptions, such as land acquisition and changes in lifestyle. Some communities experienced a temporary decrease in income during the construction process. Positive impacts identified were flood control, provision of clean water sources, and improved infrastructure in the area. However, there were negative impacts such as environmental damage, social disruption due to land acquisition, and temporary economic impacts for businesses around the project. the construction of drainage on D.I Panjaitan road has a significant impact on the socio-economic aspects of the community. It is therefore recommended that the government and related parties pay attention to the views and needs of the community in decision-making and project implementation needs to be improved, as well as more intensive socialization efforts regarding the benefits and objectives of drainage development.